Analisis pengaruh dana desa dan indeks pembangunan manusia per kabupaten/kota terhadap pertumbuhan ekonomi regional di Indonesia - Tio Andri Prasetyo; Agung Dinarjito (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2021)
The objective of this research is toanalyze the effect of the Village Fund and Human Development Index on Regional Economy with Regional Distribution as a control variable. In conducting this research, panel data from secondary data is processed using quantitative methods. This study uses a total of 1716 data consisting of 429 cross sections of data with a time series within a period of 4 years. The method used for data analysis is Feasible General Least Square (FGLS) with the Panel-Corrected Standard Errors (PCSE) estimation coefficient using Eviews10 application program. The results of the study prove that the Village Fund andHuman Development Index variable have a positive impact on Regional Economic Growth.